Analysis of Budget Deficits and Macroeconomic Fundamentals: A VAR-VECM Approach - Manamba Epaphra (Journal of Economics and Management, 2017)
Aim/purpose - This paper examines the relationship between budget deficits and selected macroeconomic variables in Tanzania for the period spanning from 1966 to 2015. Design/methodology/approach - The paper uses Vector autoregression (VAR) - Vector Error Correction Model (VECM) and variance decomposition techniques. The Johansen's test is applied to examine the long run relationship among the variables under study. Findings - The Johansen's test of cointegration indicates that the variables are cointegrated and thus have a long run relationship. The results based on the VAR-VECM estimation show that real GDP and exchange rate have a negative and significant relationship with budget deficit whereas inflation, money supply and lending interest rate have a positive one. Variance decomposition results show that variances in the budget deficits are mostly explained by the real GDP, followed by inflation and real exchange rate. Research implications/limitations - Results are very indicative, but highlight the importance of containing inflation and money supply to check their effects on budget deficits over the short run and long-run periods. Also, policy recommendation calls for fiscal authorities in Tanzania to adopt efficient and effective methods of tax collection and public sector spending. Originality/value/contribution - Tanzania has been experiencing budget deficit since the 1970s and that this budget deficit has been blamed for high indebtedness, inflation and poor investment and growth. The paper contributes to the empirical debate on the causal relationship between budget deficits and macroeconomic variables by employing VAR-VECM and variance decomposition approaches.